2-[3-(2-aminoethylsulfanyl)propylsulfanyl]ethanamine bearing dansyl subunits: An efficient, simple, and rapid fluorometric sensor for the detection of mercury(II) ions - Nantanit Wanichacheva (2018)
A novel fluorometric sensor possessing two dansyl moieties based on 2-[3-(2-aminoethylsulfanyl)propylsulfanyl]ethanamine 1 was prepared by a ready synthetic approach using a conventional two-step synthesis. 1 exhibits highly sensitive and selective on-off Hg2+fluorescence quenching behavior in aqueous acetonitrile solutions and is shown to discriminate various competing metal ions such as Cu2+, Ag+, Ca2+, Mn2+, Zn2+, Ba2+, Cd2+, Co2+, Na+, and K+exhibiting a detection limit of 7 nM. or 1.4 ppb with a working range of 1.8-15 ppb. © 2010 The Chemical Society of Japan.